Ultrasound-assisted adsorption of Pb ions by carbonized/activated date stones from singles/mixed aqueous solutions - Nora Sedira; Saliha Bouranene; Abdalhak Gheid (Elsevier, 2021)
This work aims to assess the adsorption efficiency of date stones biowaste subjected to carbonization and activation processes for the removal of Pb ions from single and mixed solutions. Several techniques have been used for characterization of adsorbents such as scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), methylene blue index and point of zero charge (pHpzc). An excellent adsorption capacity of 97.43% is achieved at an initial concentration of 300 mg/L, solution volume 75 mL of Pb nitrate, adsorbent mass of 0.7 g, temperature of 30 _C, a stirring speed of 500 rpm/min, a contact time of 180 min and pH 6. Specifically, a comparison has been conducted between carbonized/activated date stones “CADS” and commercial activated carbon “CAC” besides investigating the influence of the presence of Co ions and the utilization of ultrasound radiation. A higher adsorption rate of 98.16% is reached under ultrasound radiation at Pb(II) initial concentration of 100 mg/L for a contact time of 3 h. Nevertheless, the temperature has shown a negative effect; the adsorption rate decreases from 98.31% at 18 _C to 92.70% at 60 _C. The modeling of the experimental adsorption data manifests a type-L isotherm characteristic of Langmuir and Freundlich models. The kinetic study has shown that the experimental data are well described by a pseudo-second-order rate model and controlled by the internal diffusion, a limiting-step that controls the transfer rate of Pb(II) to the adsorbent surface. The calculated thermodynamic parameters (ΔG0, ΔH0, ΔS0) indicate that the adsorption of Pb(II) is spontaneous and exothermic process.